Perceived Impact of Social Media Influencers on Consumer Perception and Buying Behavior on Inland Resort Products and Services: An Explanatory Sequential Mixed Method Study - Cristine Mae G. Montenegro; Nenette D. Padilla (Philippine Social Science Journal, 2025)
Situated within the growing influencer marketing landscape of the Philippine tourism industry, this study utilized an explanatory sequential mixed-method approach to examine how social media influencers (SMIs) shape consumer perception and buying behavior for inland resorts in Negros Occidental. Analysis of 389 surveys and 12 interviews indicated that SMIs have a very high impact on guests across demographics, with characteristics such as credibility, trustworthiness, and attractiveness serving as key drivers for engagement and booking decisions. These results demonstrate that influencers create a comprehensive ecosystem that guides the customer journey from awareness to post-purchase satisfaction, offering inland resorts a framework to optimize digital marketing strategies. Future research should expand on this by conducting comparative analyses of influencer tiers and platform-specific effects across broader hospitality sectors.